An economic perspective on crime, its costs, crime fighting and rehabilitation efforts - Strohmeier, Peter (2010)
This study will examine the economic issues surrounding crime and reintegration measures aimed at prisoners, particularly but not exclusively in Germany. To do so it will be necessary to give an overview about the crime and crime-fighting situation in Germany. The focus is on violent and street crime. White collar crime will be mentioned only briefly. The starting point will be to examine the cost of crime and the problems concerning its measurement. These include for example the economic costs of murder or the largely ignored cost of rehabilitating the victims of crimes such as rape. They often suffer from severe trauma. Further it will prove necessary to add the indirect, immaterial costs of crime and the private expenditure on security to the direct costs of crime such as public security expenditure on police and prisons. In order to provide an economic framework for the understanding of crime use will be made of the Becker model of crime. It basically regards crime as a consequence of rational agents reacting to illegal activities yielding higher expected returns than legal ones. One of its main predictions being that a high likelihood of detection and conviction is a major deterrent. The explanatory power of the Becker model (and its limits) will be explored by looking at various aspects of crime and by looking at crimes that provide the offenders with a utility level that no legal alternative can provide from the offenders' perspective. Further, an overview over various crime related topics such as guns and drugs will be provided. A short excursion looks at the role psychology and happiness play in Becker's theory. This model is tested by looking at commonly encountered criminological facts. Also its implications for crime reduction efforts in prevention, deterrence and rehabilitation will be outlined. The special focus will be on volunteers and their link to the economic model of crime. The conclusion stresses three main aspects: Firstly the importance of further research to improve the estimates of the costs of crime; secondly the role Becker's theory can play in informing crime reducing activities by the police, the legal system as well as the labour market and education policies; and thirdly the necessity to establish a nationwide, longterm data bank for recidivism. Such a data bank is a crucial precondition for any meaningful cost-benefit analysis of reintegration and prevention measures.